Bonding Performance for Repairs Using Bulk Fill and Conventional Methacrylate Composites - Benzi, Janaina Galvão; Pucci, César Rogério [UNESP]; Freitas, Maiara Rodrigues; Suzy Liporoni, Priscila Christiane; Zanatta, Rayssa Ferreira (Hindawi, 2021)
This study compared the bond strength of a composite repair made with a bulk fill composite and a conventional one using different surface treatments. Specimens were prepared as truncated cones (bases: 4 mm × 2 mm, height: 4 mm) using a bulk fill (OBFa: Filtek One) or a conventional resin (FTKa: Filtek Z250) (n = 66). They were artificially aged (10,000 cycles, 5°C-55°C, 30 sec) and subdivided according to surface treatments: NT - no treatment (control), Abr - abrasion with a diamond tip, and sand - sandblasting with aluminum oxide (50 μm). Treatments were performed over the smaller diameter surface, followed by adhesive (Scothbond Universal) application. A new specimen with similar dimensions was constructed over it using either the OBF or the FTK, totaling 12 groups (n = 11). Bond strength was assessed by tensile test. The data were submitted to two-way ANOVA separately for OBFa and FTKa, followed by Tukey's test (p<0.05). For the aged OBFa groups, there was significant differences for composite type and surface treatment, with higher values of bond strength when repaired with the same material (OBFa/OBF > OBFa/FTK), and sandblasting and bur abrasion presented higher values compared to the control group (NT). For the aged FTKa groups, there were no differences for the composite or surface treatment. Therefore, the bulk fill resin composite tested present better repair performance when the same composite was used, while the conventional resin composite was less influenced by the material and the surface treatment performed.